Niezależność sądu oraz niezawisłość sędziowska w sprawach karnych w okresie rządów autorytarnych i totalitarnych w Polsce - Nowicki, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
At present, there is no doubt that a need exists to ensure the citizens’ right to have a criminal case examined by an independent and unbiased court. For the proper functioning of the court-based administration of justice to be possible, the courts must have the attribute of independence and the judges must be autonomous. These issues are regulated in international treaties to which Poland is a party. The aim of this study is to describe the role of judiciary independence and judicial autonomy in criminal cases. In order to achieve these goals, considerations will be presented on the essence of such independence and autonomy, and a reference will be made to the way the authoritarian state functioned after the May coup in the Second Polish Republic, and the totalitarian state during the era of the Polish People’s Republic.
Keywords: independence of the judiciary; judicial autonomy; tripartite division of powers; criminal proceedings